Reserarch progress of vasogenic white matter lesions (血管源性脑白质病变的研究进展) - FU Chao (付超); YANG Yanni (杨燕妮); LIU Chunyan (刘春燕); LI Yanjun (李艳君); GENG Qingwen (耿庆文) (中西医结合护理)
White Matter Lesion is a common imaging manifestation in the current clinical MRI (Magnetic Resonance Imaging) examination, especially in elderly patients. The etiology is complex and the clinical manifestations are different. The white matter lesions may increase the risk of stroke, mental and emotional disorders, motor dysfunction and cognitive dysfunction, seriously affecting patients’ quality of life. This article reviews the correlation between WML and MRI from the aspects of histopathology, pathophysiological mechanism and age, hypertension, sleep quality, physical activity and cognitive disorder, analyzes influencing factors of white matter lesions in elderly people, and provides reference for diagnosis, treatment and prognosis of the disease. (脑白质病变(WML)在是一种在老年人群中常见的影像学改变, 是脑小血管病的影像学特征之一, 病因复杂, 临床表现不一, 若未能及时干预, 可进展为脑卒中、精神情感异常、运动功能障碍以及认知功能障碍等, 严重影响患者生活质量。本研究从病理组织学、病理生理机制及年龄、高血压、睡眠质量、体力活动及认知障碍等方面与WML的相关性进行综述, 进一步分析老年患者发生WML的影响因素, 以为相关诊断、治疗及预后提供数据参考。)